Healthcare workers’ perceptions of patient safety culture in emergency departments: a scoping review - Min Ji Kim; Ming Wei Jeffrey Woo (BMJ Open)
Objective This review aimed to map the concept of patient safety culture in emergency departments (EDs), describe the availability of evidence related to patient safety culture as assessed by healthcare workers, identify the key focus areas of existing studies and pinpoint gaps in the current literature.Design A scoping review followed a comprehensive methodological process that included five steps based on the framework developed by Arksey and O’Malley and updated by Peters et al.Eligibility criteria Studies encompassing original research and all pertinent published and grey literature within the last 15 years (2010–2024) that aligned with the population (healthcare workers), concept (patient safety culture) and context (emergency department) framework for this study were included.Data sources PubMed, CINAHL (EBSCOhost), WOS, Embase, MEDLINE (Ovid), and KISS databases were searched for original studies published between 2010 and 2024 that aligned with the topic of this study.Data extraction and synthesis Two researchers independently extracted data from 28 eligible articles using a predetermined data extraction tool. A third researcher reviewed the data to ensure accuracy.Results A total of 28 articles were included in the review. The findings indicated an increase in research on patient safety culture in emergency departments since 2021. However, no eligible studies have assessed it within North America. Teamwork within units was the most positively perceived dimension, whereas the reporting of patient safety incidents was the least positively perceived dimension.Conclusions Although research on patient safety culture in eergency departments has increased, the findings remain limited in their generalisability due to a lack of diverse methodologies. Qualitative studies are needed to deepen the understanding of patient safety culture in multifaceted contexts. This review contributes to the academic field by bringing us closer to developing tailored interventions that can foster a positive patient safety culture in emergency departments.Protocol registration The protocol for this scoping review was registered in the Open Science Framework (https://osf.io/9f7qc).